Penguatan Moderasi Beragama melalui Program Literasi Ayat-Ayat Cinta Tanah Air bagi Unit Dakwah Kampus Unair - Safi’i, Imam; Chodir, Fatkul; Bunyamin, Bunyamin (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: Strengthening Religious Moderation Through the Literacy Program on Love for the Motherland Verses for the Da'wah Unit, Airlangga University Surabaya Campus. Methodology: The problem-based service-learning method is used in this service. This method was applied in an effort to solve community partner problems. Results: The service participants consisted of 30 people, including Unair Islamic Spirituality UKM, Ulul Azmi mosque activists, and KH Abdul Chalim University students. The place of service was at the Ulul Azmi Unair mosque and held for four meetings. This activity is based on the diversity of unfair students who are infiltrated by the existence of the results of the implementation of service learning. This shows that strengthening religious moderation through literacy of verses about love of the homeland for Islamic Spiritual UKM can become capital in national, state, and religious life, demonstrated by national commitment, having an attitude of tolerance and acceptance of tradition in the midst of society with extremist, radicalist, and liberalist ideologies. Limitations: This article may only focus on one university, namely Airlangga University (Unair), so the findings and recommendations produced cannot be generalized to other campuses or other regions that have different cultural and social contexts. Contribution: The literacy program of verses of love for the homeland can instill the values of religious moderation in students, which is expected to reduce the potential for radicalization and intolerance in the campus environment.